Peran Farmasi Klinis Pada Rekonsiliasi Untuk Mengurangi Ketidaksesuaian Pengobatan - Nailah Mutiara Wahid; Nungki Hatit Isafani; Nisful Lailatun Nadiroh; Dwi Roisiyah; Ria Fitriyanti Putri; Jesika Diah Pitaloka; Meiva Shafa Herdini; Iftitah Nakhlah Sani; Wishnu Eka Adiwinata; Bella Fevi Aristia; Alfu Laila; Eka Putri Nurhidayah; Arya Sigit Kharismawan (Jurnal Sains Farmasi Dan Kesehatan, 2026)
Medication reconciliation is an essential process in pharmaceutical care aimed at preventing medication discrepancies that may lead to medication errors and compromise patient safety. Clinical pharmacy plays a strategic role in this process through verifying, identifying, and clarifying patients’ medication histories. This review aims to analyze the role of clinical pharmacists in medication reconciliation to reduce medication discrepancies based on various research findings. This study used a literature review method by examining 10 journals related to medication reconciliation, medication discrepancies, and the role of clinical pharmacists in hospital settings. The results show that medication discrepancies are still frequently found at different stages of care, particularly during patient transitions. The most common discrepancies include omitted medications, dose differences, therapeutic duplication, and undocumented medication changes. The involvement of clinical pharmacists has been shown to reduce discrepancies through medication verification, interprofessional communication, and support from information systems and complete documentation. In conclusion, clinical pharmacists play an important role in improving the effectiveness of medication reconciliation and reducing medication discrepancies. Strengthening the role of clinical pharmacists, improving documentation systems, and enhancing interprofessional collaboration are essential to improve patient safety.